The new BELUGA setup for collocated turbulence and radiation measurements using a tethered balloon: first applications in the cloudy Arctic boundary layer - U. Egerer; M. Gottschalk; H. Siebert; A. Ehrlich; M. Wendisch (Atmospheric Measurement Techniques, 2019)
The new BELUGA (Balloon-bornE moduLar Utility for profilinG the lower Atmosphere) tethered balloon system is introduced. It combines a set of instruments to measure turbulent and radiative parameters and energy fluxes. BELUGA enables collocated measurements either at a constant altitude or as vertical profiles up to 1.5 km in height. In particular, the instrument payload of BELUGA comprises three modular instrument packages for high-resolution meteorological, wind vector and broadband radiation measurements. Collocated data acquisition allows for estimates of the driving parameters in the energy balance at various heights. Heating rates and net irradiances can be related to turbulent fluxes and local turbulence parameters such as dissipation rates. In this paper the technical setup, the instrument performance, and the measurement strategy of BELUGA are explained. Furthermore, the high vertical resolution due to the slow ascent speed is highlighted as a major advantage of tethered balloon-borne observations. Three illustrative case studies of the first application of BELUGA in the Arctic atmospheric boundary layer are presented. As a first example, measurements of a single-layer stratocumulus are discussed. They show a pronounced cloud top radiative cooling of up to 6 K h −1 . To put this into context, a second case elaborates respective measurements with BELUGA in a cloudless situation. In a third example, a multilayer stratocumulus was probed, revealing reduced turbulence and negligible cloud top radiative cooling for the lower cloud layer. In all three cases the net radiative fluxes are much higher than turbulent fluxes. Altogether, BELUGA has proven its robust performance in cloudy conditions of the Arctic atmospheric boundary layer.